Enablers for Organizational Project Management in the Chinese Context. Issue 1 (February 2016) - Wen, Qi; Qiang, Maoshan
This study aims at exploring the organizational enablers (OEs) for organizational project management (OPM) in the Chinese context. From the resource-based view of firms, we conceptualize OEs as important drivers for the business value creation processes in project-based organizations. The preliminary factor framework was constructed through literature review and expert interviews. Questionnaire surveys elicited 146 responses from Chinese project management practitioners; thereafter, factor analysis was performed to test the OE system empirically. The resulting final OE system contains 49 enablers in nine categories for three management hierarchies; this OE system, constructed by exploratory analysis and verified by confirmatory analysis, comprehensively clarifies the framework of OEs in the Chinese context; it facilitates further investigations into the interaction among OEs and their effects on organization performance. Firm managers may also find this system helpful in formulating identifiable, measurable, and manageable OE frameworks for their own firms, and enabling their organization's strategies with robust OEs.